Changes in n-acetyglucosamine content associated with capacitation and chemotaix in porcine spermatozoa - Diana, A. (2021)
In mammals, only a small number of ejaculated spermatozoa (SPZ) reach the region of the oviduct (ampulla) after the copula, where they encounterand fertilize the egg. It has been suggested that a sperm subpopulation is selected during their transit trough the female genital tract, so that only thosewith high fertilizing capability and the best skills for supporting embryo development can fertilize the egg. Fluids of the female genital tract, such asthe follicular (FF), the oviductal fluid (OF), and the secretion of cumulus-oocyte complex (COCs), could promote the SPZ chemotaxis to thefertilization site. Progesterone (P4) is considered as an effective chemoattractant in most mammalian species, though other components of the fluidscould attract SPZ even more efficiently. In the present study, we evaluated possible changes in carbohydrate composition of sperm surface aftercapacitation and chemotaxis. For this, we determined the content of N-acetyl-glucosamine (NAG) in porcine SPZ after the mentioned processes byusing WGA-FITC lectin and flow cytometry. We observed that NAG content was significantly higher in the capacitated SPZ (30 min in capacitationmedia TALP, at 38.5ºC and with 5% CO2) compared to fresh SPZ or SPZ stored in BTS (diluent media). For the chemotaxis assays, OF and FFcollected from prepubertal gilts (OF0 and FF0) and periovulatory phase (OF2 and FF2) were used as chemoattractants. Six wells were filled withfresh spermatozoa (20×106/mL) from fertile boars (N = 3) selected in a discontinuous percoll gradient and immediately transferred to TALP,previously equilibrated at 38.5ºC and 5% CO2. The opposite wells of the chemotaxis chamber (six) were filled with TALP (control group) or TALPsupplemented with the chemoattractants as indicated: (1) TALP (control), (2) FF0 (1.25%), (3) FF2 (1.25%), (4) OF0 (1.25%), (5) OF2 (1.25%), (6)P4 (28.3 pM). After 20 min at 38.5ºC and 5% CO2, the SPZ from the opposite wells were rescued, processed for NAG detection and analyzed byflow cytometry. We observed that NAG content was significantly lower in the SPZ obtained from the groups 3 and 6 compared to the control groupor the original SPZ (P < 0.05). These preliminary results suggest that FF2 and P4 can selectively attract a SPZ subpopulation with low content ofNAG in the plasma membrane under the in-vitro conditions.